Microscopic Analysis of Chipped Stone Tools from Barton Ramie, British Honduras - Wilk, Richard (Estudios de Cultura Maya, 2013)
This paper was originally intented to be a firm functional base for the re-organization of the standard Kidder-Coe typology of Mayan stone tools, through the use of wear-pattern analysis. In the present state however, this paper is only a bare beginning due to the limited nature of the assemblage examined. In the future I hope to combine re-examinations of existing collections with the trial classification of an entire collection excavated by the Corozal Proyect under Dr. Norman Hammond's direction. Re-examinations of published material will be presented in the same way as this report, and in the case of Seibal collections, Dr. Gordon Willey has invited me to present my analysis as an appendix to his own report. Eventually, it is hoped, a taxonomic system for Mayan stone tools will be evolved which reflects as closely as possible the original uses to which the tools were put. This system should, in turn, make progressively more sophisticated statistical and distributional analysis possible.